Mosquitoes OH4Surveillance 2025 - Anders Lindström (National Veterinary Institute, 2026)
Mosquitoes collected in Skåne, Sweden within the project OH4Surveillance, 2025.
Keywords: Occurrence; Specimen; OCCURRENCE; Biological Sciences; Biologi